The Effect Family Ownership on Firm Risk: The Role of Professional CEO - Andriani, Wery; Hermawan, Ancella Anitawati (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2023)
This study aims to examine whether family ownership impacts firm risk. This argument is due to the uniqueness of the family company in running its business, which prioritizes not only financial aspects but also non-financial aspects. In addition, this study also aims to examine the moderating effect of the professional CEO on the relationship between family ownership and firm risk. The samples used in this study are family firms in manufacturing industry, listed on the Indonesia Stock Exchange from 2015 to 2019. The total 245 observation will be tested with Panel Data regression. The results found that family ownership has a negative effect on firm risk. The result indicates that the company tries to maintain the family's wealth. In addition, professional CEOs are able to act more realistically and independently, thus weakening the relationship between family ownership and firm risk. In practice, the results of this study are expected to help various stakeholders understand how family ownership can affect firm risk.